2007
DOI: 10.1016/j.cellbi.2007.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological contamination in stem cell cultures

Abstract: Cell therapy and regenerative medicine are potentially two of the most exciting aspects of the novel therapeutic methods currently under development. However, these treatments present a number of important biosafety issues, like the possible transmission of microorganisms to the recipients. The most common potential form of contamination in these cell products is by bacteria (including Mycoplasma), yeast and fungi. In our study, 32 stem cell lines and feeder cell lines were analysed. There were 19 contaminated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 13 publications
0
26
0
Order By: Relevance
“…In an analysis of 32 stem cell lines and feeder cell lines, there were 19 contaminated cell passages (12%) -the main contaminants were gram positive cocci and Mycoplasma species, followed by gram negative rods and gram positive rods. 2 In this study, the Mycoplasma contamination rate was 4%. The microbial contamination of hematopoietic stem cell products may lead to potentially fatal complication of hematopoietic stem cell transplantation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an analysis of 32 stem cell lines and feeder cell lines, there were 19 contaminated cell passages (12%) -the main contaminants were gram positive cocci and Mycoplasma species, followed by gram negative rods and gram positive rods. 2 In this study, the Mycoplasma contamination rate was 4%. The microbial contamination of hematopoietic stem cell products may lead to potentially fatal complication of hematopoietic stem cell transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Lotto-lot variation in hormones and growth factors in sera, presence of endotoxins in water or sera or other culture additives (trypsin, amino acids etc), free radicals generated in media by the photo-activation of tryptophan, riboflavin or HEPES exposed to fluorescent light can all spoil a culture medium. 7 Residues from germicides used to disinfect incubators, equipments and labs, and impurities in gases used in CO 2 incubators have also been found to affect cell culture. 8 However, the major source of microbial contamination is documented to arise by contact with non-sterile supplies, media and solution, chemicals and equipments, and by the particulate matter and aerosols that fall out during transportation and incubation.…”
Section: Microbial Contamination Of Cell Culture: Incidences and Sourcesmentioning
confidence: 99%
“…Therefore, they must be prepared continuously. Additionally, the traits of mEFs differ from batch to batch, and quality control of mEFs, especially for mycoplasma contamination, may be the problems [86,87]. Moreover, hFFs are more durable than mEFs in that they remain in healthy condition more than 2 weeks after inactivation by radiation.…”
Section: Feeder Cellsmentioning
confidence: 99%
“…Blood borne pathogen standards are not limited to HIV and HBV; they also include the entire spectrum of adventitious agents in cell-based process and product development activities. For example, Cobo et al (2007) reported microbial contamination in stem cell cultures by bacteria (including Mycoplasma), yeast, and fungi. This study, based on an analysis of 32 stem cell and feeder cell lines, revealed contamination of nearly 12 percent of the cell lines mainly with gram-positive cocci and Mycoplasma species, followed by gram-negative rods.…”
Section: Articlesmentioning
confidence: 99%